PEMBINAAN TERITORIAL DESA DI KECAMATAN BALAI JAYA KABUPATEN ROKAN HILIR TAHUN 2015 - Wibowo, Rizki; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Guidance of Territorial Center Village in Balai Jaya District of Rokan Hilir Regency in 2015 is all the effort, work, and activities related to the design, development, deployment, and control potential of the region with all its aspects conducted by the Military Command 08/Bagan Sinembah empowerment strength region in Balai Jaya District of Rokan Hilir Regency, in the interests of national defense essentially to embody Oneness People TNI and TNI fundamental duty to succeed.This research was conducted in Balai Jaya Distric of Rokan Hilir Regency which is one target area Military Command 08/Bagan Sinembah. The method used in this research is descriptive qualitative method, which in this study researchers tried to explain the implementation of The Guidance of Territorial Center Village in Balai Jaya District of Rokan Hilir Regency in 2015 were carried out using three methods The Guidance of Territorial Center, namely Bhakti TNI, Fostering Resilience Region, and the Development of Social Communication. The data collection techniques in this study using the technique of in-depth interviews and documentation relevant facts and data collection about The Guidance of Territorial Center Village in Balai Jaya District of Rokan Hilir Regency in 2015. Furthermore, the data obtained from the study site will be processed and analyzed further by way of outlining the facts which has been found from the study site.From the interview to the informant and based on the data and information obtained by researchers when doing research on-site research, it can be concluded that the implementation of The Guidance of Territorial Center Village in Balai Jaya District of Rokan Hilir Regency in 2015, conducted by the Military Command 08/Bagan Sinembah, has not been implemented optimally, there are still some obstacles in its implementation, both internally and externally. Inhibiting factors internal include: infrastructure is inadequate, there is a lack of personnel, the low level of welfare Babinsa, while factors external resistor among others : components outside the military who do not fully understand the coaching Territorial Army, as well as the influence globalization and the times that make awareness to defend the country, patriotism, and national awareness among the people especially the younger generation, increasingly weakened.Keywords: The Guidance Of Territorial Center, Military Command, Defence Area Empowerment